Electrolyte and lithium ion battery
By using an electrolyte containing carboxylic acid ester and benzenesulfonyl isocyanate compounds in lithium-ion batteries, the shortcomings in fast charging and cycling performance of lithium-ion batteries are solved, and a more stable SEI film and higher battery performance are achieved.
Patent Information
- Application Number
- CN202411955155.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-27
- Publication Date
- 2025-04-18
AI Technical Summary
There are shortcomings in the fast charging and circulation performance of existing lithium-ion batteries, especially the low lithium ion diffusion rate of lithium iron phosphate batteries, which leads to polarization and SEI film instability, affecting the circulation performance of the battery.
An electrolyte including carboxylic acid ester and benzenesulfonyl isocyanate compounds is used. The electrolyte enhances the stability of the SEI film by reducing the viscosity of the electrolyte and improving the conductivity, thereby improving the fast charging and cycling performance of the lithium-ion battery.
The electrolyte forms a stable SEI film in a lithium-ion battery, reducing lithium ion losses, improving the fast charging and cycling performance of the battery, and especially showing good chemical stability and capacity retention rate at high temperatures.
Smart Images

Figure CN119852521A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of lithium batteries, and in particular, to electrolytes and lithium-ion batteries. Background Art
[0002] Lithium-ion battery technology is one of the important energy storage technologies in today's society. Lithium-ion batteries are widely used in electric vehicles, military equipment, aerospace, energy storage systems and other fields. The electrolyte in lithium batteries plays a vital role and needs to be well compatible with the electrodes and diaphragms in lithium-ion batteries to connect the batteries into an organic whole. The composition of the electrolyte can have a direct impact on the electrochemical properties of lithium-ion batteries. Therefore, by optimizing the electrolyte formula, the performance of lithium-ion batteries can be optimized.
[0003] It should be noted that the above statements are only used to provide background technical information related to the present application and do not necessarily constitute prior art. Summary of the invention
[0004] In a first aspect of the present application, the present application proposes an electrolyte, comprising: a solvent and an additive, wherein the solvent comprises a carboxylate; the additive comprises a benzenesulfonyl isocyanate compound, and the benzenesulfonyl isocyanate compound satisfies Formula 1:
[0005]
[0006] Among them, R1, R2, R3, R4, and R5 are independently selected from any one of H, F, Cl, Br, methyl, ethyl, propyl, butyl, pentyl, and hexyl.
[0007] Therefore, the electrolyte proposed in this application has appropriate liquid fluidity and high ion conductivity. Moreover, in lithium-ion batteries, after the electrolyte decomposes to form an SEI film layer, the SEI layer has good stability, reducing the loss of lithium ions caused by repeated generation of SEI film rupture and the changes in the composition and structure of the SEI layer in lithium-ion batteries. Therefore, the electrolyte proposed in this application is conducive to improving the fast charging performance and cycle performance of lithium-ion batteries.
[0008] In some embodiments, R1, R2, R3, R4, and R5 are independently selected from any one of H, methyl, ethyl, and propyl. In Formula 1, R1, R2, R3, R4, and R5 are within the aforementioned functional group range, and the benzene ring in the benzenesulfonyl isocyanate compound has a strong reactivity with R1, R2, R3, R4, and R5, and can form a strong interaction with the α-H introduced by the carboxylate in the electrolyte, thereby reducing the effect of α-H on the SEI film. As a result, the benzenesulfonyl isocyanate compound additive can improve the stability of the electrolyte in the lithium-ion battery, thereby improving the cycle performance of the lithium-ion battery.
[0009] In some embodiments, the benzenesulfonyl isocyanate compound includes at least one of p-toluenesulfonyl isocyanate, benzenesulfonyl ester isocyanate, o-toluenesulfonyl isocyanate, and m-toluenesulfonyl isocyanate.
[0010] The aforementioned compound has a hydrogen bond acceptor that can form a hydrogen bond, and forms a hydrogen bond interaction with the α-H introduced by the carboxylate, so that the electrolyte solvent has a high stability. Therefore, the electrolyte containing the aforementioned compound and the carboxylate is conducive to the formation of a chemically stable SEI film in the lithium ion battery.
[0011] In some embodiments, the mass fraction of the benzenesulfonyl isocyanate compound in the electrolyte is 0.05%-2%. Thus, the benzenesulfonyl isocyanate compound can fully exert the role of carboxylic acid ester as a solvent of the electrolyte to improve the conductivity of the electrolyte, and improve the stability of the SEI film and the chemical stability of the electrolyte, which is beneficial to improving the cycle performance and high temperature storage retention rate of the lithium-ion battery.
[0012] In some embodiments, the carboxylic acid ester includes at least one of ethyl acetate, ethyl propionate, methyl acetate, and methyl propionate. Thus, the carboxylic acid ester as an electrolyte solvent can improve the wettability of the electrolyte, increase the conductivity of the electrolyte, and help improve the fast charging performance of the lithium-ion battery.
[0013] In some embodiments, the mass fraction of the carboxylic acid ester in the electrolyte is 20%-60%, which is beneficial to improve the conductivity of the electrolyte, thereby improving the fast charging performance of the lithium-ion battery.
[0014] In some embodiments, the solvent further comprises a carbonate, and the carbonate comprises at least one of ethyl methyl carbonate, ethylene carbonate, propylene carbonate, and dimethyl carbonate. Thus, the carbonate has good chemical stability and good solubility, which is beneficial to improving the chemical stability of the lithium ion battery.
[0015] In some embodiments, the solvent further comprises carbonate, and the mass fraction of the carbonate is 37.5%-62.5%. Thus, the carbonate can form a stable mixed solvent with the carboxylic acid ester.
[0016] In some embodiments, the electrolyte includes a lithium salt, wherein the lithium salt includes an electrolyte lithium salt and an additive lithium salt. Thus, the lithium ion content in the electrolyte can be supplemented, and the loss of lithium ions during the cycle can be compensated, which is beneficial to improving the cycle performance of the lithium-ion battery.
[0017] In some embodiments, the electrolyte lithium salt includes lithium hexafluorophosphate, and the mass fraction of the electrolyte lithium salt in the electrolyte is 8%-13%. Therefore, in the electrolyte proposed in the present application, adding electrolyte lithium salt can better supplement lithium ions, which is beneficial to improving the cycle performance of lithium-ion batteries.
[0018] In some embodiments, the additive lithium salt includes at least one of lithium bis(fluorosulfonyl)imide, lithium tetrafluoroborate, lithium difluorophosphate, lithium difluorooxalateborate, lithium dioxalateborate, lithium difluorodioxalatephosphate, and lithium tetrafluorooxalatephosphate, and the mass fraction of the additive lithium salt in the electrolyte is 1%-5%. Thus, the conductivity of the electrolyte can be improved, which helps to improve the fast charging performance of the lithium-ion battery, and effectively reduces the performance attenuation of the battery during high-temperature use, and improves the high-temperature storage retention rate of the lithium-ion battery.
[0019] In some embodiments, the additive further includes vinylene carbonate, and the mass fraction of the vinylene carbonate in the electrolyte is 0.5%-5%. Thus, vinylene carbonate as an additive is conducive to forming a stable SEI film, which can improve the cycle performance of the lithium-ion battery.
[0020] In some embodiments, the additive further includes vinyl sulfate, and the mass fraction of the vinyl sulfate in the electrolyte is 0.05%-2%. Thus, vinyl sulfate as an additive can reduce polarization in lithium-ion batteries and improve the fast charging performance of lithium-ion batteries.
[0021] In a second aspect of the present application, the present application proposes a lithium-ion battery, comprising: an electrolyte, wherein the electrolyte is the electrolyte proposed in the present application; and a positive electrode plate, wherein the positive electrode active material in the positive electrode plate comprises lithium iron phosphate.
[0022] The lithium-ion battery proposed in this application uses lithium iron phosphate as the positive electrode active material, so that the lithium-ion battery has higher stability and safety performance. Combined with the use of the electrolyte proposed in this application, the fast charging performance and cycle performance of the lithium-ion battery can be improved. Therefore, the lithium-ion battery has good performance in stability, safety, fast charging performance, and cycle performance. DETAILED DESCRIPTION
[0023] Unless otherwise defined, all technical and scientific terms used in this application have the same meanings as those commonly understood by technicians in the technical field to which this application belongs; the terms used in this application are only for the purpose of describing specific embodiments and are not intended to limit this application; unless otherwise specified, the numerical values of the parameters mentioned in this application can be measured using various measurement methods commonly used in the art (for example, they can be tested according to the methods given in the embodiments of this application).
[0024] The terms "including" and "having" in the specification and claims of the present application and any modifications thereof are open expressions, that is, including the contents specified in the present application but not excluding other contents.
[0025] In the description of this application, regardless of whether the words "about" or "approximately" are used, all the numbers disclosed herein are approximate values. The value of each number may differ by less than 10% or a reasonable difference considered by those skilled in the art, such as 1%, 2%, 3%, 4% or 5%.
[0026] "Scope" disclosed in the present application is limited in the form of lower limit and upper limit, and a given range is limited by selecting a lower limit and an upper limit, and the selected lower limit and upper limit define the boundary of a special range. The scope limited in this way can be including end values or not including end values, and can be arbitrarily combined, that is, any lower limit can be combined with any upper limit to form a scope. For example, if the scope of 60-120 and 80-110 is listed for a specific parameter, it is understood that the scope of 60-110 and 80-120 is also expected. In addition, if the minimum range values 1 and 2 are listed, and if the maximum range values 3, 4 and 5 are listed, the following scope can be all expected: 1-3, 1-4, 1-5, 2-3, 2-4 and 2-5. In the present application, unless otherwise specified, the numerical range "ab" represents the abbreviation of any real number combination between a and b, wherein a and b are real numbers. For example, the numerical range "0-5" means that all real numbers between "0-5" are listed in this document, and "0-5" is just an abbreviation of these numerical combinations. In addition, when a parameter is expressed as an integer ≥ 2, it is equivalent to disclosing that the parameter is, for example, an integer of 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, etc.
[0027] Unless otherwise specified, all embodiments and optional embodiments of the present application can be combined with each other to form a new technical solution.
[0028] Unless otherwise specified, all technical features and optional technical features of this application can be combined with each other to form a new technical solution.
[0029] Lithium iron phosphate material (LiFePO4 or LFP) is used as the positive electrode active material of lithium-ion batteries. It is widely used in electric vehicles, energy storage systems and other fields due to its high safety, good cycle stability, non-toxic and environmentally friendly, low cost and other advantages. However, compared with ternary materials, lithium iron phosphate has a lower lithium ion diffusion rate and lower electronic conductivity. Lithium-ion batteries with lithium iron phosphate as the positive electrode active material, i.e., lithium iron phosphate batteries, are prone to polarization during the charging and discharging process, which limits the development and application of lithium-ion batteries with lithium iron phosphate as the positive electrode active material in the field of fast charging.
[0030] In order to reduce the migration resistance of lithium ions in lithium iron phosphate materials and increase the diffusion rate of lithium ions, the chemical composition of the electrolyte in the lithium iron phosphate battery can be adjusted to use low-viscosity, high-ionic conductivity components to improve the migration ability of lithium ions. Compared with carbonate solvents in the electrolyte, carboxylates as electrolyte solvents have lower viscosity and better wettability, which can improve the conductivity of the electrolyte and help improve the fast charging performance of lithium-ion batteries.
[0031] However, the adjustment of the chemical composition of the electrolyte will also have a certain impact on the formation and stability of the solid electrolyte interface film (SEI film) in the lithium-ion battery. In lithium iron phosphate batteries, carbonates decompose and react with lithium ions in the electrolyte to form a stable SEI film on the surface of the negative electrode. Carboxylic acid esters, as solvents, account for a large proportion of the electrolyte, and a large amount of α-H connected to carbonyl carbon is introduced into the electrolyte, and α-H is reactive. The presence of a large amount of α-H in the electrolyte causes the formed SEI film to be repeatedly destroyed and re-reacted, affecting the stability of the SEI film, thereby causing the consumption of lithium ions and the reduction of the cycle performance of the lithium-ion battery. In order to solve the aforementioned problems, the present application proposes an electrolyte and a lithium-ion battery. The electrolyte proposed in the present application has a high electrolyte conductivity, which is beneficial to improving the fast charging performance of the lithium-ion battery; at the same time, the electrolyte proposed in the present application can react to form a stable SEI film, which is beneficial to improving the cycle performance of the lithium-ion battery.
[0032] In a first aspect of the present application, the present application proposes an electrolyte, comprising: a solvent and an additive, wherein the solvent comprises a carboxylate; the additive comprises a benzenesulfonyl isocyanate compound, and the benzenesulfonyl isocyanate compound satisfies Formula 1:
[0033]
[0034] Among them, R1, R2, R3, R4, and R5 are independently selected from any one of H, F, Cl, Br, methyl, ethyl, propyl, butyl, pentyl, and hexyl.
[0035] The electrolyte proposed in the present application includes a carboxylate as an electrolyte solvent. The carboxylate has a low viscosity, which reduces the steric hindrance of lithium ion migration in lithium-ion batteries, so that the electrolyte has a higher conductivity, thereby improving the fast charging performance of lithium-ion batteries. Benzenesulfonyl isocyanate compound additives are added to the electrolyte. The isocyanate group (-NCO) contained in the benzenesulfonyl isocyanate compound can react with water and / or acid in the lithium-ion battery to generate a urea substance that is insoluble in the solvent, thereby effectively improving the stability of the SEI film. Benzenesulfonyl isocyanate compounds satisfy Formula 1, can interact with the α-H of the carboxylate, reduce the activity of α-H, improve the stability of the SEI film, and make the electrolyte have good chemical stability at high temperature, so as to improve the cycle performance of the lithium-ion battery and the capacity retention rate at high temperature. As a result, the electrolyte proposed in the present application has appropriate liquid fluidity and high electrolyte conductivity. Moreover, in lithium-ion batteries, after the electrolyte decomposes to form an SEI film layer, the SEI layer has good stability, reducing the loss of lithium ions caused by repeated generation of the SEI film rupture and the changes in the composition and structure of the SEI layer of the lithium-ion battery. Therefore, the electrolyte proposed in this application is conducive to improving the fast charging performance and cycle performance of lithium-ion batteries.
[0036] In some embodiments, R1, R2, R3, R4, and R5 are independently selected from any one of H, methyl, ethyl, and propyl. In Formula 1, R1, R2, R3, R4, and R5 are within the aforementioned functional group range, and the benzene ring in the benzenesulfonyl isocyanate compound has a strong reactivity with R1, R2, R3, R4, and R5, and can form a strong interaction with the α-H introduced by the carboxylate in the electrolyte, thereby reducing the effect of α-H on the SEI film. As a result, the benzenesulfonyl isocyanate compound additive can improve the stability of the electrolyte in the lithium-ion battery, thereby improving the cycle performance of the lithium-ion battery.
[0037] In some embodiments, the benzenesulfonyl isocyanate compound includes at least one of p-toluenesulfonyl isocyanate, benzenesulfonyl ester isocyanate, o-toluenesulfonyl isocyanate, and m-toluenesulfonyl isocyanate.
[0038] include:
[0039] (methylbenzenesulfonyl isocyanate),
[0040] (Benzenesulfonyl isocyanate),
[0041] (o-Toluenesulfonyl isocyanate),
[0042] (m-Toluenesulfonyl isocyanate);
[0043] The aforementioned compound has a hydrogen bond acceptor that can form a hydrogen bond, and forms a hydrogen bond interaction with the α-H introduced by the carboxylate, so that the electrolyte solvent has a high stability. Therefore, the electrolyte containing the aforementioned compound and the carboxylate is conducive to the formation of a chemically stable SEI film in the lithium ion battery.
[0044] In some embodiments, the mass fraction of the benzenesulfonyl isocyanate compound in the electrolyte is 0.05%-2%. The mass fraction of the benzenesulfonyl isocyanate compound within the aforementioned range can interact with the α-H introduced by the carboxylate to limit the damage of the SEI film by the α-H. As a result, the benzenesulfonyl isocyanate compound can fully exert the role of the carboxylate as a solvent of the electrolyte to improve the conductivity of the electrolyte, improve the stability of the SEI film and the chemical stability of the electrolyte, and is conducive to improving the cycle performance and high temperature storage retention rate of the lithium-ion battery.
[0045] In some embodiments, the carboxylate includes at least one of ethyl acetate (EA), ethyl propionate (EP), methyl acetate (MA), and methyl propionate (MP). The aforementioned carboxylate is used as an electrolyte solvent, and its liquid viscosity is low, the surface tension is small, it has good solubility in lithium salts, and has a wide liquid temperature range. Therefore, the aforementioned carboxylate as an electrolyte solvent can improve the wettability of the electrolyte, increase the conductivity of the electrolyte, and is conducive to improving the fast charging performance of the lithium-ion battery.
[0046] In some embodiments, the mass fraction of the carboxylic acid ester in the electrolyte is 20%-60%. Carboxylic acid ester is used as an electrolyte solvent, and its mass fraction is within the above range, which can adjust the viscosity of the electrolyte and the solubility of the electrolyte in lithium salts, which is beneficial to improve the liquid fluidity of the electrolyte and increase the lithium ion content in the electrolyte. Therefore, it is beneficial to improve the conductivity of the electrolyte, thereby improving the fast charging performance of the lithium-ion battery.
[0047] In some embodiments, the solvent further includes a carbonate, and the carbonate includes at least one of ethyl methyl carbonate (EMC), ethylene carbonate (EC), propylene carbonate (PC), and dimethyl carbonate (DMC). The aforementioned carbonate, as an electrolyte solvent, can react with lithium to form an organic SEI film of alkyl lithium carbonate. Carbonate has good chemical stability and good solubility, which is conducive to the full dissolution of additives, lithium salts and other substances added to the electrolyte. As a result, it is conducive to improving the chemical stability of lithium-ion batteries.
[0048] In some embodiments, the solvent further includes carbonate, and the mass fraction of the carbonate is 37.5%-62.5%. The mass fraction of carbonate is within the aforementioned range, because carbonate has good versatility and can dissolve additives, lithium salts and other substances in the electrolyte well. Thus, carboxylic acid esters can form a stable mixed solvent with carboxylic acid esters.
[0049] In some embodiments, the electrolyte includes a lithium salt, wherein the lithium salt includes an electrolyte lithium salt and an additive lithium salt. Thus, the lithium ion content in the electrolyte can be supplemented, and the loss of lithium ions during the cycle can be compensated, which is beneficial to improving the cycle performance of the lithium-ion battery.
[0050] In some embodiments, the electrolyte lithium salt includes lithium hexafluorophosphate, and the mass fraction of the electrolyte lithium salt in the electrolyte is 8%-13%. The electrolyte lithium salt is ionized in the electrolyte solvent to release a large amount of lithium ions. The lithium ions in the electrolyte can be supplemented, and the lithium ions, as carriers of charge transfer during the battery charging and discharging process, participate in the redox reaction between the positive and negative electrodes of the battery. Further, in the electrolyte proposed in the present application, the additive includes a benzenesulfonyl isocyanate compound, and the benzenesulfonyl isocyanate compound contains a sulfonyl group (-SO2-) that can delocalize the electrons on the nitrogen atom connected thereto. Thereby blocking the reaction of lithium hexafluorophosphate lithium salt decomposition to generate PF5 in the presence of moisture or caused by increased temperature, reducing the generation of LiF and HF, and then helping to inhibit the activity of carboxylic acid esters at the negative electrode interface, which helps to inhibit the decomposition of the electrolyte at the electrode interface. Therefore, in the electrolyte proposed in the present application, adding an electrode liquid lithium salt can better supplement lithium ions, which is beneficial to improving the cycle performance of lithium ion batteries.
[0051] In some embodiments, the additive lithium salt includes at least one of lithium bis(fluorosulfonyl)imide, lithium tetrafluoroborate, lithium difluorophosphate, lithium difluorooxalate borate, lithium dioxalate borate, lithium difluorodioxalate phosphate, and lithium tetrafluorooxalate phosphate, and the mass fraction of the additive lithium salt in the electrolyte is 1%-5%. The aforementioned additive lithium salt has a strong ionic conductivity and can improve the mobility of lithium ions in the electrolyte. The fluoride ions in lithium bis(fluorosulfonyl)imide (LiFSI) have strong electron-withdrawing properties, and the coordination effect between anions and cations in the lithium salt is weak, which can enhance the mobility of lithium ions in the electrolyte. LiFSI has excellent thermal stability and reduces the possibility of side reactions such as thermal decomposition in high temperature environments. As a result, the conductivity of the electrolyte can be improved, which helps to improve the fast charging performance of lithium-ion batteries, and effectively reduces the performance attenuation of the battery during high-temperature use, and improves the high-temperature storage retention rate of lithium-ion batteries.
[0052] In some embodiments, the additive further includes vinylene carbonate, and the mass fraction of the vinylene carbonate in the electrolyte is 0.5%-5%. Vinylene carbonate (VC) in the electrolyte is conducive to the formation of a SEI film with high lithium ion conductivity and stable chemical properties, which can reduce the occurrence of side reactions of the electrolyte at the negative electrode of the lithium ion battery, and is conducive to improving the cycle performance of the lithium ion battery. The formed SEI film helps to reduce the interface resistance between the lithium ion battery electrode and the electrolyte, so that lithium ions can be more smoothly embedded and removed from the electrode surface during the charge and discharge process. As a result, it is conducive to the formation of a stable SEI film, which can improve the cycle performance of the lithium ion battery.
[0053] In some embodiments, the additive further includes vinyl sulfate, and the mass fraction of the vinyl sulfate in the electrolyte is 0.05%-2%. Vinyl sulfate (DTD) can coordinate with lithium salts and lithium ions in the solvent to form a stable complex in the electrolyte, and further form a dense SEI film on the electrode surface, effectively inhibiting the irreversible reaction between the electrode material and the electrolyte, protecting the electrolyte, and improving the cycle life of the battery. DTD in the electrolyte can improve the wettability of the electrolyte, which is beneficial to improving the contact and electron transmission performance of the electrode / electrolyte interface. Therefore, vinyl sulfate as an additive can reduce the polarization phenomenon in lithium-ion batteries and improve the fast charging performance of lithium-ion batteries.
[0054] In some embodiments, the additive includes at least one of fluoroethylene carbonate (FEC), methylene disulfonate (MMDS), 1,3 propane sultone (PS), tris(trimethylsilyl) phosphate (TMSP), tris(trimethylsilyl) borate (TMSB), lithium difluorooxalatoborate (LiODFB), and lithium difluorophosphate (LiPO2F2). The aforementioned additives are conducive to the formation of a relatively stable SEI film in lithium-ion batteries, and are conducive to balancing the high-temperature storage performance, high-temperature cycle performance, low-temperature power performance, and low-temperature charging capacity of lithium-ion batteries.
[0055] In a second aspect of the present application, the present application proposes a lithium-ion battery, comprising: an electrolyte, wherein the electrolyte is the electrolyte proposed in the present application; and a positive electrode plate, wherein the positive electrode active material in the positive electrode plate comprises lithium iron phosphate.
[0056] The lithium-ion battery proposed in this application uses lithium iron phosphate as the positive electrode active material. The PO bond in the lithium iron phosphate crystal is stable, which makes the lithium-ion battery have higher stability and safety performance. Combined with the use of the electrolyte proposed in this application, it can improve the electrolyte conductivity and chemical stability, which is conducive to improving the fast charging performance of the lithium-ion battery and shortening the charging time of the lithium-ion battery at room temperature. At the same time, the electrolyte proposed in this application can improve the stability of the SEI film in the lithium-ion battery. As a result, the lithium-ion battery has good performance in stability, safety, fast charging performance, and cycle performance.
[0057] In some embodiments, the charging cut-off voltage of the lithium-ion battery is less than or equal to 3.75 V. Within the aforementioned charging cut-off voltage range, the cycle performance and safety of the lithium-ion battery are at a relatively good level.
[0058] The scheme of the present application is described below by specific examples. It should be noted that the following examples are only used to illustrate the present application and should not be considered as limiting the scope of the present application. If no specific technology or conditions are specified in the examples, the technology or conditions described in the literature in this area or the product instructions are used. The reagents or instruments used are not specified by the manufacturer, and are all conventional products that can be obtained commercially.
[0059] Example 1
[0060] S1: Preparation of electrolyte:
[0061] Lithium salt: 3% by mass of LiFSI, 10% by mass of LiPF6, additives: 2% by mass of VC, 1% by mass of DTD, 0.5% by mass of toluenesulfonyl isocyanate, 1% by mass of FEC, carboxylate: 40% by mass of EA, carbonate: 28% by mass of EC, 14.5% by mass of EMC, are mixed in a glove box or a dry room according to the above mass fractions to prepare an electrolyte;
[0062] S2: Preparation of positive electrode sheet:
[0063] The positive electrode material LiFePO4, the binder polyvinylidene fluoride (PVDF), and the conductive agent acetylene black were mixed in a mass ratio of 94:3:3, and N-methylpyrrolidone (NMP) solvent was added until the system became uniform and transparent. The positive electrode material slurry was prepared by stirring with a vacuum mixer. The positive electrode material slurry was evenly coated on the positive electrode current collector aluminum foil (thickness of 13 μm), dried at room temperature, and then transferred to a 120°C oven for drying for 1 h, and then cold pressed (compacted density of 2.6 g / cm 3 ), cutting to obtain the positive electrode sheet;
[0064] S3: Preparation of negative electrode sheet
[0065] The negative electrode material graphite, the thickener sodium carboxymethyl cellulose solution, and the binder styrene butadiene rubber latex were mixed in a mass ratio of 96:2:2, and deionized water solvent was added. The negative electrode material slurry was prepared by stirring with a vacuum mixer. The negative electrode material slurry was evenly coated on the current collector copper foil (thickness of 6 μm), dried at room temperature, and then transferred to a 120°C oven for drying for 1 h, and then cold pressed (compacted density of 1.6 g / cm 3 ) and cut to obtain the negative electrode sheet.
[0066] S4: Lithium-ion battery preparation
[0067] The positive electrode sheet, the negative electrode sheet and the polypropylene separator are wound, wrapped with an aluminum-plastic film, baked to remove water, and then the prepared electrolyte is injected and sealed. After standing, hot and cold pressing, formation, clamping, capacity division and other processes, a soft-pack lithium-ion battery is prepared.
[0068] Example 2
[0069] Example 2 is consistent with Example 1, except that, in S1, lithium salt: 1% by mass of LiFSI, 8% by mass of LiPF6, additives: 2% by mass of VC, 1% by mass of DTD, 0.5% by mass of methylbenzenesulfonyl isocyanate, 1% by mass of FEC, carboxylate: 40% by mass of EA, carbonate: 28% by mass of EC, 18.5% by mass of EMC.
[0070] Example 3
[0071] Example 3 is consistent with Example 1, except that, in S1, lithium salt: 5% by mass of LiFSI, 13% by mass of LiPF6, additives: 2% by mass of VC, 1% by mass of DTD, 0.5% by mass of methylbenzenesulfonyl isocyanate, 1% by mass of FEC, carboxylate: 40% by mass of EA, carbonate: 28% by mass of EC, 18.5% by mass of EMC.
[0072] Example 4
[0073] Example 4 is consistent with Example 1, except that, in S1, lithium salt: 3% by mass of LiFSI, 10% by mass of LiPF6, additives: 2% by mass of VC, 1% by mass of DTD, 0.5% by mass of methylbenzenesulfonyl isocyanate, 1% by mass of FEC, carboxylate: 20% by mass of EA, carbonate: 28% by mass of EC, 34.5% by mass of EMC.
[0074] Example 5
[0075] Example 5 is consistent with Example 1, except that, in S1, lithium salt: 3% by mass of LiFSI, 10% by mass of LiPF6, additives: 2% by mass of VC, 1% by mass of DTD, 0.5% by mass of methylbenzenesulfonyl isocyanate, 1% by mass of FEC, carboxylate: 60% by mass of EA, and carbonate: 22.5% by mass of EC.
[0076] Example 6
[0077] Example 6 is consistent with Example 1, except that, in S1, lithium salt: 3% by mass of LiFSI, 10% by mass of LiPF6, additives: 0.5% by mass of VC, 2% by mass of DTD, 0.5% by mass of methylbenzenesulfonyl isocyanate, 3% by mass of FEC, carboxylate: 40% by mass of EA, carbonate: 28% by mass of EC, 13% by mass of EMC.
[0078] Example 7
[0079] Example 7 is consistent with Example 1, except that, in S1, lithium salt: 3% by mass of LiFSI, 10% by mass of LiPF6, additives: 5% by mass of VC, 0.05% by mass of DTD, 0.5% by mass of methylbenzenesulfonyl isocyanate, 1% by mass of FEC, carboxylate: 40% by mass of EA, carbonate: 28% by mass of EC, 12.45% by mass of EMC.
[0080] Example 8
[0081] Example 8 is consistent with Example 1, except that, in S1, lithium salt: 3% by mass of LiFSI, 10% by mass of LiPF6, additives: 2% by mass of VC, 1% by mass of DTD, 0.05% by mass of methylbenzenesulfonyl isocyanate, 1% by mass of FEC, carboxylate: 40% by mass of EA, carbonate: 28% by mass of EC, 14.05% by mass of EMC.
[0082] Example 9
[0083] Example 9 is consistent with Example 1, except that, in S1, lithium salt: 3% by mass of LiFSI, 10% by mass of LiPF6, additives: 2% by mass of VC, 1% by mass of DTD, 2% by mass of methylbenzenesulfonyl isocyanate, 1% by mass of FEC, carboxylate: 40% by mass of EA, carbonate: 28% by mass of EC, 13% by mass of EMC.
[0084] Example 10
[0085] Example 10 is consistent with Example 1, except that, in S1, lithium salt: 3% by mass of LiFSI, 10% by mass of LiPF6, additives: 2% by mass of VC, 1% by mass of DTD, 0.5% by mass of methylbenzenesulfonyl isocyanate, 1% by mass of FEC, carboxylate: 40% by mass of EP, carbonate: 28% by mass of EC, 14.5% by mass of EMC.
[0086] Embodiment 11
[0087] Example 11 is consistent with Example 1, except that, in S1, lithium salt: 3% by mass of LiFSI, 10% by mass of LiPF6, additives: 2% by mass of VC, 1% by mass of DTD, 0.5% by mass of methylbenzenesulfonyl isocyanate, 1% by mass of FEC, carboxylate: 40% by mass of MA, carbonate: 28% by mass of EC, 14.5% by mass of EMC.
[0088] Example 12
[0089] Example 12 is consistent with Example 1, except that, in S1, lithium salt: 3% by mass of LiFSI, 10% by mass of LiPF6, additives: 2% by mass of VC, 1% by mass of DTD, 0.5% by mass of methylbenzenesulfonyl isocyanate, 1% by mass of FEC, carboxylate: 40% by mass of MP, carbonate: 28% by mass of EC, 14.5% by mass of EMC.
[0090] Embodiment 13
[0091] Example 13 is consistent with Example 1, except that, in S1, lithium salt: 3% by mass of LiFSI, 10% by mass of LiPF6, additives: 2% by mass of VC, 1% by mass of DTD, 0.5% by mass of methylbenzenesulfonyl isocyanate, 0.5% by mass of FEC, 0.5% by mass of MMDS, carboxylate: 40% by mass of EA, carbonate: 28% by mass of EC, 14.5% by mass of EMC.
[0092] Embodiment 14
[0093] Example 14 is consistent with Example 1, except that, in S1, lithium salt: 3% by mass of LiFSI, 10% by mass of LiPF6, additives: 2% by mass of VC, 1% by mass of DTD, 0.5% by mass of methylbenzenesulfonyl isocyanate, 0.5% by mass of FEC, 0.5% by mass of PS, carboxylate: 40% by mass of EA, carbonate: 28% by mass of EC, 14.5% by mass of EMC.
[0094] Embodiment 15
[0095] Example 15 is consistent with Example 1, except that, in S1, lithium salt: 3% by mass of LiFSI, 10% by mass of LiPF6, additives: 2% by mass of VC, 1% by mass of DTD, 0.5% by mass of methylbenzenesulfonyl isocyanate, 0.5% by mass of FEC, 0.5% by mass of TMSP, carboxylate: 40% by mass of EA, carbonate: 28% by mass of EC, 14.5% by mass of EMC.
[0096] Example 16
[0097] Example 16 is consistent with Example 1, except that, in S1, lithium salt: 3% by mass of LiFSI, 10% by mass of LiPF6, additives: 2% by mass of VC, 1% by mass of DTD, 0.5% by mass of methylbenzenesulfonyl isocyanate, 0.5% by mass of FEC, 0.5% by mass of TMSB, carboxylate: 40% by mass of EA, carbonate: 28% by mass of EC, 14.5% by mass of EMC.
[0098] Embodiment 17
[0099] Example 17 is consistent with Example 1, except that, in S1, lithium salt: 3% by mass of LiFSI, 10% by mass of LiPF6, additives: 2% by mass of VC, 1% by mass of DTD, 0.5% by mass of methylbenzenesulfonyl isocyanate, 0.5% by mass of FEC, 0.5% by mass of LIODFB, carboxylate: 40% by mass of EA, carbonate: 28% by mass of EC, 14.5% by mass of EMC.
[0100] Embodiment 18
[0101] Example 18 is consistent with Example 1, except that, in S1, lithium salt: 3% by mass of LiFSI, 10% by mass of LiPF6, additives: 2% by mass of VC, 1% by mass of DTD, 0.5% by mass of methylbenzenesulfonyl isocyanate, 0.5% by mass of FEC, 0.5% by mass of LIPO2F2, carboxylate: 40% by mass of EA, carbonate: 28% by mass of EC, 14.5% by mass of EMC.
[0102] Comparative Example 1
[0103] Comparative Example 1 is consistent with Example 1, except that, in S1, lithium salt: 12.5% by mass of LiPF6, additives: 2% by mass of VC, 1% by mass of FEC, 0.3% by mass of LIPO2F2, no carboxylate, carbonate: 28% by mass of EC, 19.7% by mass of EMC, 5% by mass of PC, and 32% by mass of DMC.
[0104] The electrolyte components in Examples 1 to 18 and Comparative Example 1 can be found in Table 1.
[0105] Table 1
[0106]
[0107]
[0108] Test method:
[0109] 1. Electrolyte conductivity test
[0110] The prepared electrolyte was placed in a constant temperature water bath at 25°C for 30 min, and the conductivity was tested with a conductivity meter.
[0111] 2. 1C cycle test at 45℃
[0112] At 45°C, the prepared lithium-ion battery was first discharged at 1C to 2.0V and then subjected to a cycle test.
[0113] The test process is to first charge to 3.75V at 1C constant current, then charge at constant voltage to a current of 0.05C, and then discharge to 2.0V at 1C constant current. The charge / discharge cycle is repeated to calculate the capacity retention rate of the lithium-ion battery after 1000 cycles of 1C / 1C at 45°C.
[0114] 3. 4C cycle test at 25℃
[0115] At 25°C, the prepared lithium-ion battery was first discharged at 1C to 2.0V and then subjected to a cycle test.
[0116] The test process is to first charge to 3.75V at 4C constant current, then charge at constant voltage to a current of 0.05C, and then discharge to 2.0V at 1C constant current. The charge / discharge cycle is repeated to calculate the capacity retention rate of the lithium-ion battery after 500 cycles of 1C / 1C at 25°C.
[0117] 4. Storage test at 60°C
[0118] At 25°C, the prepared lithium-ion battery was first discharged at 1C to 2.0V, then charged at 1C constant current to 3.75V, then charged at constant voltage to a current of 0.05C, and then discharged at 1C constant current to 2.0V. The discharge capacity is recorded as C. 放1 The lithium-ion battery is then charged to 3.75V at 1C constant current, and then charged to 0.05C at constant voltage. The lithium-ion battery is stored in a 60°C oven for 60 days, and then placed at room temperature, first discharged to 2.0V at 1C, then charged to 3.75V at 1C constant current, then charged to 0.05C at constant voltage, and then discharged to 2.0V at 1C constant current. The discharge capacity is recorded as C. 放2 .
[0119] C 放2 / C 放1 ×100% = Capacity retention rate (%)
[0120] Test results: See Table 2
[0121] Table 2
[0122]
[0123]
[0124] From Table 2, we can see that:
[0125] Compared with Example 1, the electrolyte proposed in the present application can significantly improve the conductivity of the lithium-ion battery and meet the 6C charging capacity. In Comparative Example 1, lithium precipitation occurred during the 6C cycle, and the loss of active lithium increased, causing the battery cell to dive; in Example 1, due to the synergistic effect of additive formula 1-1 and carboxylic acid ester, the damage of carboxylic acid ester to the negative electrode interface can be effectively inhibited, so the 1C cycle capacity retention rate at 45°C is significantly improved.
[0126] Compared with Example 1 and Comparative Example 2, in Comparative Example 2, there is no additive formula 1-1, the stability of the SEI film of the lithium ion battery decreases, and the capacity retention rate of 1C cycle at 45°C and storage for 60D at 0°C is significantly reduced.
[0127] The changes in lithium salt content in Examples 2 and 3 also significantly improve the 6C cycle performance compared to Comparative Example 1.
[0128] Compared with Comparative Example 1, Example 5 has a higher carboxylate content and the conductivity of the electrolyte is significantly improved.
[0129] Compared with Example 1, the VC content of Example 6 and Example 7 decreases and increases, and the capacity of the lithium-ion battery after 1C cycle at 45°C and storage at 0°C for 60D remains unchanged relative to that of 500cls after 6C cycle at 25°C.
[0130] Compared with Example 1, the content of the compound of Formula 1-1 in Example 8 and Example 9 has changed. The content of the compound of Formula 1-1 has decreased, and the high-temperature storage and cycle have significantly deteriorated, and the 6C cycle retention rate has significantly deteriorated, indicating that it effectively inhibits the decomposition of the electrolyte at the electrode interface in the electrode liquid, which is conducive to the formation of a stable SEI layer.
[0131] In Examples 10 to 12, carboxylates of EP, MA, and MP are used respectively. Compared with Comparative Example 1, the high-temperature cycle capacity retention rate, high-temperature storage performance, and 6C cycle of the lithium-ion battery are greatly improved.
[0132] Compared with Example 1, Example 13-Example 18 respectively adds additives MMDS, PS, TMSP, TMSP, LiODFB, and LiPO2F2, which are conducive to forming a stable SEI film and can balance the high temperature storage performance, high temperature cycle performance, and fast charging performance of lithium-ion batteries.
[0133] In the description of the present application, "A and / or B" may include the case of A alone, the case of B alone, or any of the cases of A and B, where A and B are only used for examples and may be any technical feature connected by "and / or" in the present application.
[0134] In the description of this application, "same chemical composition" should be understood in a broad sense, that is, the main components of the two have the same chemical composition, or the chemical composition of the two is basically the same, and may have errors within the allowable range in the field that are understandable to those skilled in the art or contain impurities within the allowable range.
[0135] In the present application, the writing order of each step does not mean a strict execution order and does not constitute any limitation on the implementation process. The specific execution order of each step should be determined by its function and possible internal logic. If there is no special explanation, all steps of the present application can be performed sequentially or randomly, preferably sequentially. For example, the method includes steps (a) and (b), indicating that the method may include steps (a) and (b) performed sequentially, or may include steps (b) and (a) performed sequentially. For example, the method may also include step (c), indicating that step (c) can be added to the method in any order, for example, the method may include steps (a), (b) and (c), or may include steps (a), (c) and (b), or may include steps (c), (a) and (b), etc.
[0136] It should be noted that the present application is not limited to the above-mentioned embodiments. The above-mentioned embodiments are only examples, and the embodiments having the same structure as the technical idea and exerting the same effect within the scope of the technical solution of the present application are all included in the technical scope of the present application. In addition, without departing from the scope of the main purpose of the present application, various modifications that can be thought of by those skilled in the art to the embodiments and other methods of combining some of the constituent elements in the embodiments are also included in the scope of the present application.
Claims
1. An electrolyte, characterized in that: include: Solvents, additives, among which The solvent includes a carboxylic acid ester; The additive includes a benzenesulfonyl isocyanate compound, and the benzenesulfonyl isocyanate compound satisfies Formula 1: Among them, R1, R2, R3, R4, and R5 are independently selected from any one of H, F, Cl, Br, methyl, ethyl, propyl, butyl, pentyl, and hexyl.
2. The electrolyte according to claim 1, characterized in that R1, R2, R3, R4, and R5 are each independently selected from any one of H, methyl, ethyl, and propyl.
3. The electrolyte according to claim 2, characterized in that The benzenesulfonyl isocyanate compound includes at least one of p-toluenesulfonyl isocyanate, benzenesulfonyl ester isocyanate, o-toluenesulfonyl isocyanate and m-toluenesulfonyl isocyanate.
4. The electrolyte according to claim 1, characterized in that The mass fraction of the benzenesulfonyl isocyanate compound in the electrolyte is 0.05%-2%.
5. The electrolyte according to any one of claims 1 to 4, characterized in that The carboxylic acid ester comprises at least one of ethyl acetate, ethyl propionate, methyl acetate and methyl propionate; and / or, The mass fraction of the carboxylic acid ester in the electrolyte is 20%-60%.
6. The electrolyte according to any one of claims 1 to 4, characterized in that: The solvent further comprises a carbonate, and the carbonate comprises at least one of ethyl methyl carbonate, ethylene carbonate, propylene carbonate, and dimethyl carbonate; and / or, The solvent further comprises carbonate, and the mass fraction of the carbonate is 37.5%-62.5%.
7. The electrolyte according to any one of claims 1 to 4, characterized in that: The electrolyte includes lithium salt, wherein the lithium salt includes electrolyte lithium salt and additive lithium salt.
8. The electrolyte according to any one of claim 7, characterized in that include: The electrolyte lithium salt comprises lithium hexafluorophosphate, and the mass fraction of the electrolyte lithium salt in the electrolyte is 8%-13%; and / or, The additive lithium salt includes at least one of lithium bis(fluorosulfonyl)imide, lithium tetrafluoroborate, lithium difluorophosphate, lithium difluorooxalatoborate, lithium dioxalatoborate, lithium difluorodioxalatophosphate, and lithium tetrafluorooxalatophosphate. The mass fraction of the additive lithium salt in the electrolyte is 1%-5%.
9. The electrolyte according to any one of claims 1 to 4, characterized in that: The additive further comprises vinylene carbonate, and the mass fraction of the vinylene carbonate in the electrolyte is 0.5%-5%; and / or, The additive further includes vinyl sulfate, and the mass fraction of the vinyl sulfate in the electrolyte is 0.05%-2%.
10. A lithium ion battery, characterized in that: include: An electrolyte, wherein the electrolyte is the electrolyte according to any one of claims 1 to 9; A positive electrode plate, wherein the positive electrode active material in the positive electrode plate includes lithium iron phosphate.
Citation Information
Patent Citations
Battery electrolyte and preparation method thereof, lithium sulfur secondary battery
CN109167096A
High-voltage lithium cobalt oxide lithium ion battery non-aqueous electrolyte and lithium ion battery
CN115763971A
Electrolyte and battery
CN117199533A
Electrolyte for lithium ion battery with improved low-temperature performance and ultra-fast charging lithium ion battery
CN117293397A
Electrolyte and lithium ion battery using same
CN117790890A
Cited By
Electrolyte and battery
CN120376757A
Electrolyte and lithium ion battery
WO2026137790A1